2021
DOI: 10.20870/oeno-one.2021.55.2.4657
|View full text |Cite
|
Sign up to set email alerts
|

Impact of <i>Lachancea thermotolerans</i> strain and lactic acid concentration on <i>Oenococcus oeni</i> and malolactic fermentation in wine

Abstract: The yeast Lachancea thermotolerans can produce lactic acid during alcoholic fermentation (AF) and thereby acidify wines with insufficient acidity. However, little is known about the impact of L. thermotolerans on Oenococcus oeni, the primary lactic acid bacterium used in malolactic fermentation (MLF). This study explored the impact of sequential cultures of L. thermotolerans and Saccharomyces cerevisiae on MLF performance in white and red wines. Four L. thermotolerans strains were tested in Sauvignon blanc wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 55 publications
(85 reference statements)
3
31
0
Order By: Relevance
“…The S. cerevisiae control produces 30% less glycerol than the sequential fermentations between Concerto and S. cerevisiae. Other studies have reported non-significant differences for the three studied commercial L. thermotolerans strains in sequential fermentations, while the S. cerevisiae control produces 15% less glycerol [15].…”
Section: Glycerolmentioning
confidence: 73%
See 4 more Smart Citations
“…The S. cerevisiae control produces 30% less glycerol than the sequential fermentations between Concerto and S. cerevisiae. Other studies have reported non-significant differences for the three studied commercial L. thermotolerans strains in sequential fermentations, while the S. cerevisiae control produces 15% less glycerol [15].…”
Section: Glycerolmentioning
confidence: 73%
“…Recent studies have compared some of the different available commercial strains (Levulia TM , AEB, Italy; Concerto TM , CHR Hansen, Denmark; Laktia TM , Lallemand, Canada) [14][15][16], showing interesting differences and even contradictory results regarding several enological parameters, depending on the study. According to all of them, sequential fermentation using L. thermotolerans and S. cerevisiae is more efficient than co-inoculation as far as lactic acid production is concerned.…”
Section: Thermotolerans Commercial Strains Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations